Analysis of international tourist arrivals in China: The role of World Heritage Sites - Yang, Chih-Hai; Lin, Hui-Lin; Han, Chia-Chun (Tourism management (1982), 2010)
This paper analyzes the determinants of international tourist arrivals in China, especially for World Heritage Sites and various kinds of travel spots. Utilizing annual provincial panel data over the 2000–2005 period, the empirical results suggest that key determinants include the relative income, population in the original country, cost of travel, and tourism infrastructure. In addition, World Heritage Sites are also found to be significant in explaining the numbers of international tourists and have a greater tourist-enhancing effect. Other famous tourist sites rated 4A- and 3A-class are also attractive to foreign tourism. Moreover, cultural rather than natural sites attract more interest among foreign tourists, because China is internationally renowned for its long-standing historical and cultural assets. Finally, the importance of the determinants of the demand for tourism varies from country to country.